POLITIK PANGAN DI ERA GLOBALISASI - Adirini Pujayanti (Sekretariat Jenderal DPR RI, 2011)
Food is an important commodity since it has a direct impact on human life. This paper argues that cheap food rezime has disappeared due to uncontrolled population growth while at the same time there is a decreasing production caused by the lessening land farming and global warming. Food crisis can affect instability of national security, which in turn implicates world peace. It also argues that a nation with a good food security policy has a better position in the international politics. Indonesia as a developing country has to stand on its own feet, if the country does not want to fall into the food trap of developed country on today’s free trade era.